2002
DOI: 10.1111/1471-0366.00039
|View full text |Cite
|
Sign up to set email alerts
|

Policy Regimes and Performance of the Agricultural Sector in Latin America and the Caribbean During the Last Three Decades

Abstract: In a review of the policy regimes and agricultural output performance in Latin America and the Caribbean (LAC) during the past three decades, the linear sequence of pre-reform, crisis and reform, and post-reform recovery is qualified, focusing on a sample of nine LAC countries. The sector did quite well during the ISI policy regime, criticized for its price discrimination, and does not show the assumed characteristics of the 'lost decade' during most of the 1980s, as even agricultural exports (in constant term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…First, some of the basic pro-market criticisms of the stateled land reform that, in turn, form part of the premises for the pro-market model are quite problematic (see Borras, e.g., 2003c). For example: the criticism pertaining to the top-down, "supply-driven" approaches in land reform that claims that lands were not really demanded by peasants is problematic, especially when many land reforms have actually been actively "demanded" by poor peasants; the criticism that the use of coercive approaches is said to be a cause of land reform failures is problematic because most land reforms with higher degrees of success were those that employed highly coercive measures; the assumption that the inward-looking orientation of agricultural policies during the Import-Substitution Industrialization (ISI) were among the causes of the failure of agrarian reforms is problematic because in fact the records of both inward-looking and outward-looking development strategies were mixed (see, e.g., Spoor, 2002;Kay, 2002b;Gwynne and Kay, 2004;Bryceson, Kay and Mooij, 2000;Saith, 1990).…”
Section: Beyond the Limits-centred And Opportunities-centred Perspectmentioning
confidence: 99%
“…First, some of the basic pro-market criticisms of the stateled land reform that, in turn, form part of the premises for the pro-market model are quite problematic (see Borras, e.g., 2003c). For example: the criticism pertaining to the top-down, "supply-driven" approaches in land reform that claims that lands were not really demanded by peasants is problematic, especially when many land reforms have actually been actively "demanded" by poor peasants; the criticism that the use of coercive approaches is said to be a cause of land reform failures is problematic because most land reforms with higher degrees of success were those that employed highly coercive measures; the assumption that the inward-looking orientation of agricultural policies during the Import-Substitution Industrialization (ISI) were among the causes of the failure of agrarian reforms is problematic because in fact the records of both inward-looking and outward-looking development strategies were mixed (see, e.g., Spoor, 2002;Kay, 2002b;Gwynne and Kay, 2004;Bryceson, Kay and Mooij, 2000;Saith, 1990).…”
Section: Beyond the Limits-centred And Opportunities-centred Perspectmentioning
confidence: 99%
“…In the early 1990s the rural livelihoods approach emerged as a way to overcome some of the shortcomings of prevalent theories of rural development which were 19 Max Spoor (2001Spoor ( , 2002 has shown that the performance of agriculture has been better under ISI than after liberalization. The price discrimination against agriculture during ISI was compensated by favourable supportive measures that largely favoured large farmers but also benefited some smallholders and which neoliberal thinkers have failed to take fully into account in their critique of ISI, see Krueger et al (1991) as well as Schiff and Valdés (1998). considered either too economistic (as in the neoclassical view) or too deterministic and structuralist (as in the Marxist view).…”
Section: Rural Livelihoods: Emerging New Paradigm?mentioning
confidence: 99%
“…21 In other words, while agricultural prices may have been artificially depressed because of an overvalued exchange rate and export taxes, this was to varying degrees redressed through positive resource transfers into the sector via public investment, subsidised credit and agricultural services. 22 Meanwhile, industrial growth, which has historically been the sine qua non of massive poverty reduction by absorbing the labour force that is released from agriculture, has remained anaemic in recent decades in developing countries, with the exception of East Asia. 23 Indeed, one of the remarkable features of structural change in contemporary developing countries has been the disproportionate shift of the labour force from agriculture to 'services' (rather than to industry), which is ominous, as much of this can be thinly disguised survival strategies indicative of a desperate effort to turn to anything that might be available (which happens to fall into the 'services' rubric).…”
Section: Livelihoods In the Era Of Liberalisationmentioning
confidence: 99%